The 2015 Greek bailout referendum as a protest action: an analysis of media representations of the 'yes' and 'no' campaigns - Manavopoulos, Vasilis; Triga, Vasiliki (My University, 2017)
In the early summer of 2015, it was especially easy to feel frustrated with the state of the Greek media. Polarisation in public discourse reached its apex on 27 June 2015, when Prime Minister Alexis Tsipras announced that a referendum was to be held a mere nine days later, on 5 July. The electorate was to decide whether the government should sign a third economic bailout plan in exchange for a refinancing of the country’s sovereign debt. In an unusual move Tsipras called on the citizens to vote ‘No’, rejecting the proposal his own government had negotiated with its creditors, commonly referred to as the ‘Troika’. Although, by now familiar with what the bulk of a third bailout programme would entail (reductions in government spending and market liberalisation), Greek citizens still had to cast a vote regarding a complex matter with a limited amount of time for deliberation. A fully informed decision would, for example, involve consideration of enigmatic ‘SMP profits’, which were ‘to be transferred from the Eurogroup’, according to the ‘Preliminary Debt Sustainability Analysis’, 1 the second of two annexes to the proposed agreement, after a fifteen-page-long referendum question. Turning to the media for help, citizens could find plentiful calls to resistance or prophesies of doom but little composed and informed analysis as suggested by evidence of previous research on media campaigns in referendums (Brady and Johnston, 2006; DeKavalla, 2016; de Vreese and Semetko, 2002).
Keywords: Referendum; Economic bailout plan; Greece; Media